Disseminated Genital and Extragenital Lichen Sclerosus et Atrophicus. A Case Report - Odisa Mildres Cortés Ros; Francisco Nelson Matos Figueredo; Trenny Gahona Kross; Lourdes Villacrés Medina (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Lichen sclerosus et atrophicus is a chronic inflammatory skin disease of unknown causes. It occurs more frequently in women between the fourth and fifth decade of life. Genital areas are a common location for this disorder; extragenital lesions are rare. In order to communicate this uncommon association, a case of a 77-year-old female patient with disseminated genital and extragenital lesions is presented. She was clinically diagnosed with disseminated genital and extragenital lichen sclerosus et atrophicus, which was confirmed by a histological study. Treatment with high-potency topical steroids was prescribed, leading to the improvement of the skin lesions and the disappearance of pruritus.